HISTORIOGRAFI ISLAM INDONESIA: METODE SEJARAH HAMKA DALAM KARYA SEJARAH DARI PERBENDAHARAAN LAMA TAHUN 1963 - M Reno Raditia (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
This article discusses about the writing of history/historiography Islam in Indonesia by focusing on Hamka as a historian based on Dari Perbendaharaan Lama. This research uses historical methods with technical library methods in order to study and analyse Hamka and his insight in historical science, as well as the historical methods used by Hamka, the sources he obtained, and approach he took. And the author finds that Hamka is quite compatible in historical science both in terms of work and from recognition of experts, as well Hamka’s historical methods in the book Dari Perbendaharaan Lama follows the historical method proposed by G.W.F. Hegel, namely method of reflective history type of pragmatic history. Hamka is an informal or non-academic historian, namely, a historian who has not studied history in depth. He is an autodidact in various sciences and knowledge. One of Hamka's areas of expertise is history, especially Islamic history; this is proven by his works in the field of history, one of which is From the Old Treasury, which was published in 1963. And not only that, Hamka's expertise in history is also recognized by academic or professional historians. Hamka, in writing history, collected his sources based on two categories, namely based on the legacy of the ancestors of the Indonesian people, such as kaba, saga, chronicle, etc., which generally contain elements of fairy tales or myths, and Hamka has his own way of interpreting them. Then, based on data from Western scholars, Hamka, who started his writing based on an Indocentric attitude, also looked at sources from Western scholars. Hamka's historical method in his book is in harmony with the historical method proposed by historian G.W.F. Hegel, namely the Reflective History method, a pragmatic historical type in which historians are able to present past events in the present. The essence of the writing is moral reflection and moral instruction through history with the hope that readers will always uphold existing moral values and prepare for the nation's future.